Test anxiety in students of CEPRE - UNMSM cycle 2012-I - Chávez Chacaltana, Hilda (2014)
The present paper had the purpose of exploring test anxiety reactions in students of the CEPRE-UNMSM 2012 - I Cycle. The instrument used to gather the data was the Test Anxie- ty Inventory (Bauermeister, Collazo & Spielberger, 1982) that evaluates emotionality and preoccupation factors. The population was constituted by 800 students using an intentional non-probability sampling. The results indicate that 27% of the students present a high level of test anxiety, whereas 33.38% of the students have a low level test anxiety and 39.63%, a moderate level. In addition to that, regarding the gender, female students had a higher level of anxiety (17,13%) over male students (9,88%). Moreover, there was higher anxiety level in candidates of the following careers: Medicine, Law and Management.